2018
DOI: 10.1002/adfm.201805094
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Shell Engineering to Achieve Optimal Photoalignment of Semiconductor Quantum Rods for Liquid Crystal Displays

Abstract: The photoalignment process to align semiconductor quantum rods (QRs) in the liquid crystal monomer (LCM) matrix is a flexible technology; however, the optical quality of the resulting enhancement films drops at high concentrations of the QRs. The compatibility between the ligand shell on the QRs and the LCM plays an important role in avoiding this issue. Herein, several kinds of ligand shells on the rod-in-rod CdSe/CdS QRs are designed, without affecting the optical properties of QRs, and their compatibility w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Particularly, for liquid crystal displays (LCD), unidirectionally aligned QRs are very promising as an enhancement film (QREF) for display backlight unit (BLU) replacing quantum dot enhancement films (QDEFs). [ 21–24 ] Because of the polarized emission, and higher light out‐coupling coefficients, QRs improve the overall optical efficiency of LCDs. [ 21,22,25 ] Three possible configurations have been explored for the QD‐based BLU for LCDs: i) edge optics proposed by QD Vision (Massachusetts), ii) QDEFs proposed by Nanosys (California); and iii) a QD‐on‐chip design proposed by LumenMax Optoelectronics (Taiwan).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, for liquid crystal displays (LCD), unidirectionally aligned QRs are very promising as an enhancement film (QREF) for display backlight unit (BLU) replacing quantum dot enhancement films (QDEFs). [ 21–24 ] Because of the polarized emission, and higher light out‐coupling coefficients, QRs improve the overall optical efficiency of LCDs. [ 21,22,25 ] Three possible configurations have been explored for the QD‐based BLU for LCDs: i) edge optics proposed by QD Vision (Massachusetts), ii) QDEFs proposed by Nanosys (California); and iii) a QD‐on‐chip design proposed by LumenMax Optoelectronics (Taiwan).…”
Section: Introductionmentioning
confidence: 99%
“…The QR ligands employed in this study are a mixture of longer octadecylphosphonic acid and shorter hexylphosphonic acid, with the ratio around 1:2. In the previous related study, it was shown that shorter ligands provide some space for the LCM to interpenetrate and interact with longer ligands …”
Section: Resultsmentioning
confidence: 99%
“…However, many practical applications rely on device-scale, tuneable polarized luminescence from thin films of QDs, which requires the formation of anisotropic, configurable assemblies with longrange order ranging from nm to mm scales. 16 Over the last two decades several tools and methods to obtain ordered, thin films of QDs (often referred to as superlattices, SL) were developed. [17][18][19][20] In the case of anisotropic nanocrystals unidirectional alignment of QDs in SL is required to coherently enhance the intrinsic directional properties of individual QDs and achieve macroscopically anisotropic fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…These QDs/LC nanocomposites allow for ordered QDs thin-film tuneability, long-range order, and exhibit directional optical properties, making them interesting for applications as low-cost ondemand single photon sources or energy-efficient displays. 16,[34][35][36][37] However, one of the key parameters determining optical quality of these devices is compatibility between the ligand shell of quantum dots and the LC matrix. 16,38,39 Along this line, several groups have recently demonstrated that precise control of the architecture of the ligand shell can lead to enhanced dispersion or tuneable organization of QDs in the LC matrix 36 , however further research on QDs/LC matrix interactions is required to fully captitalize on the potential of these devices, e.g.…”
Section: Introductionmentioning
confidence: 99%